Performance of a cold room powered about energy solar photovoltaic for the preservation of mangoes - Bignan-kagomna, Bouwèreou; Windé Nongué Koumbem , Daniel; Bagaya , Noufou; Ouedraogo , Issaka; Oumar , Sanogo (International Journal of Engineering and Technology, 2023)
This article focuses on the study of the performance of a cold room powered by photovoltaic solar energy for the preservation of agri-food products, more particularly mangoes. The objective of this work is the analysis of the thermal profiles of the cold room and the evaluation of the capacity of the latter to keep the products in good conditions. A study was carried out on the components of the cold unit as well as its operating principle. In addition, the evolution of the temperature of the cold room, depending on external conditions, was studied. Thus for an average internal temperature of the room which varies in the interval [14°C, 15°C], the Amelie mango variety is the one which loses the most mass during storage; it loses 10% of its initial mass after two weeks of storage and 15% in three weeks. The mass loss of Kent and Lippens mango varieties is approximately 4-5% in two weeks and 11-12% in three weeks. The average cooling power of approximately 3 kW and an average COP of 1.9 were established. The photovoltaic generator proved sufficient to power the cold unit.